Nonsteroidal Anti-Inflammatory Drug-Induced Gastroduodenal Bleeding: Risk Factors and Prevention Strategies - Thomas Wex; Marino Venerito; Peter Malfertheiner (MDPI AG, 2010)
Nonsteroidal anti-inflammatory drugs (NSAIDs) are the most widely prescribed medications in the World. A frequent complication of NSAID use is gastroduodenal bleeding. Risk factors for gastroduodenal bleeding while on NSAID therapy are age, prior peptic ulcer and co-medication with anti-platelet agents, anticoagulants, glucocorticosteroids and selective serotonin-reuptake inhibitors (SSRI). Prevention strategies for at-risk patients include the use of the lowest effective dose of NSAIDs, co-therapy with proton-pump inhibitors and/or the use of a COX-2 selective agent. Treatment of Helicobacter pylori infection is beneficial for primary prophylaxis of NSAID-induced gastroduodenal bleeding in NSAID-naive patients. For patients with cardiovascular risk factors requiring NSAIDs, naproxen should be selected. In very high risk patients for both gastrointestinal and cardiovascular complications NSAID therapy should be avoided altogether.